Recovery of Organic and Amino Acids from Sludge and Fish Waste in Sub Critical Water Conditions - Faisal, Muhammad; Daimon, Hiroyuki; Fujie, Koichi (Jurnal Rekayasa Kimia & Lingkungan, 2011)
The possibility of organic and amino acid production from the treatment of sludge and fish waste using water at sub critical conditions was investigated. The results indicated that at sub-critical conditions, where the ion product of water went through a maximum, the formation of organic acids was favorable. The presence of oxidant favored formation of acetic and formic acid. Other organic acids of significant amount were propionic, succinic and lactic acids. Depending on the type of wastes, formation of other organic acids was also possible. Knowing the organic acids obtained by hydrolysis and oxidation in sub-critical water of various wastes are useful in designing of applicable waste treatment process, complete degradation of organic wastes into volatile carbon and water, and also on the viewpoint of resource recovery. The production of lactic acid was discussed as well. The results indicated that temperature of 573 K, with the absence of oxidant, yield of lactic acid from fish waste was higher than sewage sludge. The maximum yield of total amino acids (137 mg/g-dry fish) from waste fish entrails was obtained at subcritical condition (T = 523 K, P = 4 MPa) at reaction time of 60 min by using the batch reactor. The amino acids obtained in this study were mainly alanine and glycine.Keywords: organic acids, amino acids, sub-critical water, hydrothermal, resources recovery